THE SOCIETAL IMPACT OF CLOUD-NATIVE IAM SYSTEMS: PRIVACY AND TRUST IN THE DIGITAL AGE - Arun Ganapathi, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article examines the societal impact of cloud-native Identity and Access Management (IAM) systems, focusing on their role in privacy protection and trust building in the digital age. The study investigates various aspects including public sector implementation, healthcare applications, privacy considerations, ethical implications, and future developments. The article highlights the transformation of digital identity management through AI-enhanced authentication, blockchain-based consent mechanisms, and privacy-preserving frameworks. The article encompasses government services, healthcare sectors, data protection strategies, and emerging technological trends, providing insights into the challenges and opportunities in implementing cloud-native IAM solutions while maintaining a balance between security, accessibility, and user privacy.